Imbalance of bacteriome profiles within the Finnish Diabetes Prediction and Prevention study: Parallel use of 16S profiling and virome sequencing in stool samples from children with islet autoimmunity and matched controls - Cinek, Ondrej; Kramna, Lenka; Lin, Jake; Oikarinen, Sami; Kolarova, Katerina; Ilonen, Jorma; Simell, Olli; Veijola, Riitta; Autio, Reija; Hyöty, Heikki (Pediatric diabetes, 2017)
BACKGROUND: We set out to explore associations between the stool bacteriome profiles and early-onset islet autoimmunity, taking into account the interactions with the virus component of the microbiome. METHODS: Serial stool samples were longitudinally collected from 18 infants and toddlers with early-onset islet autoimmunity (median age 17.4 months) followed by type 1 diabetes, and 18 tightly matched controls from the Finnish Diabetes Prediction and Prevention (DIPP) cohort. Three stool samples were analyzed, taken 3, 6, and 9 months before the first detection of serum autoantibodies in the case child. The risk of islet autoimmunity was evaluated in relation to the composition of the bacteriome 16S rDNA profiles assessed by mass sequencing, and to the composition of DNA and RNA viromes. RESULTS: Four operational taxonomic units were significantly less abundant in children who later on developed islet autoimmunity as compared to controls-most markedly the species of Bacteroides vulgatus and Bifidobacterium bifidum. The alpha or beta diversity, or the taxonomic levels of bacterial phyla, classes or genera, showed no differences between cases and controls. A correlation analysis suggested a possible relation between CrAssphage signals and quantities of Bacteroides dorei. No apparent associations were seen between development of islet autoimmunity and sequences of yet unknown origin. CONCLUSIONS: The results confirm previous findings that an imbalance within the prevalent Bacteroides genus is associated with islet autoimmunity. The detected quantitative relation of the novel "orphan" bacteriophage CrAssphage with a prevalent species of the Bacteroides genus may exemplify possible modifiers of the bacteriome.
Keywords: molekulární typizace; Male; Gastrointestinal Microbiome; Feces; RNA virová; studie případů a kontrol; Autoimmunity; autoimunita; Cohort Studies; Prospective Studies; Bacteriophages; Islets of Langerhans; Humans; Bacteroides; Molecular Typing; autoimunitní nemoci; prospektivní studie; mužské pohlaví; výpočetní biologie; RNA ribozomální 16S; Female; nemocnice univerzitní; kohortové studie; RNA, Viral; Finsko; association; bakteriofágy; Hospitals, University; virome; Case-Control Studies; Computational Biology; ženské pohlaví; Finland; RNA, Bacterial; RNA, Ribosomal, 16S; feces; bakteriální RNA; Longitudinal Studies; fylogeneze; Diabetes Mellitus, Type 1; Risk; microbiome; Dysbiosis; Autoimmune Diseases; dysbióza; diabetes mellitus 1. typu; CrAssphage; Langerhansovy ostrůvky; riziko; longitudinální studie; lidé; dítě; Phylogeny; Child; střevní mikroflóra